Opinions of Mr. Justice Harlan at the conference in Paris of the Bering Sea Tribunal of Arbitration [electronic resource] : constituted by the treaty of February 29, 1892 between Her Britannic Majesty and the United States of America, and composed of the following members : Baron de Courcel, senator annd ambassador of France, president of the tribunal; the Right Honourable Lord Hannan of Great Britain; the Honourable Sir John Thompson, minister of Justice and attorney-general of Canada; Mr. Justice Harlan, a justice of the Supreme Court of the United States; Senator Morgan, a senator of the United States; Marquis Emilio Visconti Venosta, former minister of Foreign Affairs and senator of the Kingdom of Italy and His Excellency Gregers Gram, minister of State of Norway. - Harian, John Marshall, 1833-1911 (Washington : G.P.O., 1893)
At head of title: Bering Sea Tribunal of Arbitration. Electronic reproduction. Mode of access: Internet. 44